Intraguild interactions among specialised pollen feeders and generalist phytoseiids and their effect on citrus rust mite suppression. Issue 5 (29th July 2015) - Maoz, Yonatan; Gal, Shira; Argov, Yael; Domeratzky, Sylvie; Coll, Moshe; Palevsky, Eric
Abstract: BACKGROUND: Antagonistic interactions among predators with shared prey are thought to hamper their ability to suppress herbivores. Our aim was to quantify intraguild interactions in omnivorous predatory mite assemblages in the presence of pollen, and assess their effect on pest populations. We focused on the following naturally occurring phytoseiid species in Israeli citrus orchards and their ability to suppress a key pest, the citrus rust mite (CRM) Phyllocoptruta oleivora (Eriophyidae): the generalists Amblyseius swirskii and Typhlodromus athiasae and the specialised pollen feeders Iphiseius degenerans, Euseius scutalis, E. stipulatus and E. victoriensis . Evaluations were performed on two spatial scales, tree seedlings and leaf discs. RESULTS: On seedlings, experiments were conducted to quantify the interactions between predators in the presence of pollen and its effects on CRM suppression. On leaf discs, intraguild interactions were studied between pairs of phytoseiid species in the presence of pollen without CRM. On seedlings, the specialised pollen predators were more effective at suppressing CRM populations than the generalist predators . CONCLUSION: In most cases, the more aggressive intraguild predator was the specialised pollen feeder. Similarly, leaf‐disc experiments suggest that in these interactions the specialised pollen feeders tend to be the intraguild predators more often than the intraguild prey. © 2015 Society of Chemical Industry